Colonial law in Africa, 1808-1919. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
Originally known as the 'Government Gazettes', each item contains the colonial laws for the year they were published. The legal records also include property for sale, probate records and bankruptcy notices. This is the first part of the three part series 'Colonial Law in Africa'. These items cover the Napoleonic Wars, the Boer War and the First World War. They also cover the abolition of the legal status of slavery. These gazettes were published alongside the African Blue Books of Statistics during the 19th and 20th centuries.
Date range: 1808-1919.
Keywords: Africa -- Politics and government